2002
DOI: 10.1111/j.1945-5100.2002.tb00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Noble gases in enstatite chondrites II: The trapped component

Abstract: Abstract-The trapped noble gas record of 57 enstatite chondrites (E chondrites) has been investigated. Basically, two different gas patterns have been identified dependent on the petrologic type. All E chondrites of type 4 to 6 show a mixture of trapped common chondritic rare gases (Q) and a subsolar component (range ofelemental ratios for E4-6 chondrites: 36Ar/132Xe = 582 ± 270 and 36Ar/84Kr= 242 ± 88). E3 chondrites usually contain Q gases, but also a composition with lower 36Ar/132Xe and 36Ar/84Kr ratios, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 46 publications
7
75
0
Order By: Relevance
“…These results therefore support the suggestion that sub-Q gases are elementally fractionated Q-gases (Patzer and Schultz, 2002). Patzer and Schultz (2002) found from noble gas measurements of 57 E chondrites that only five E3 chondrites show solar noble gas signatures.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results therefore support the suggestion that sub-Q gases are elementally fractionated Q-gases (Patzer and Schultz, 2002). Patzer and Schultz (2002) found from noble gas measurements of 57 E chondrites that only five E3 chondrites show solar noble gas signatures.…”
Section: Introductionsupporting
confidence: 88%
“…4) (El Goresy et al, 1988). This and the suggestion that ALH84206 is one of the most primitive E3 chondrites (Zhang et al, 1995) are consistent with the trend found by Patzer and Schultz (2002 Br (Marti et al, 1966), suggesting the presence of neutron-induced Kr. …”
supporting
confidence: 90%
See 2 more Smart Citations
“…This figure clearly illustrates that the xenon in carbonaceous chondrites is mainly carried in two solids: the phase Q and pre-solar grains, although phase Q is volumetrically by far the dominant component. Phase Q is observed in all chondrites (ordinary, carbonaceous and enstatite) (e.g., Schelhass et al, 1990;Patzer and Schultz, 2002;Okazaki et al, 2010).…”
Section: Figure 26mentioning
confidence: 99%